KYb2F7:Er3+ based nanothermometers: controlled synthesis, enhanced red emission, and improved sensitivities via crystal-site engineering. Issue 6 (31st January 2023) - Su, Shaoshan; Song, Wei; Wen, Hongli; Mo, Zhurong; Wan, Tonghua; Yu, Lin; Zhao, Weiren; Hakeem, Deshmukh Abdul
Abstract : KYb2 F7 :Er 3+ UC nanocrystal-based nanothermometers have greatly improved the S R with ion substitution of Ti 4+, Ge 4+, and Y 3+ for Yb 3+ . Abstract : KYb2 F7 nanocrystals have stimulated extensive research interest due to their unique structure and tunable upconversion (UC) properties for the development of different technological applications. Herein, the controlled synthesis of KYb2 F7 :Er 3+ nanocrystals for precise control over the crystal phases and morphologies was realized by varying the KF dose and reaction time via a facile hydrothermal method. Upon 365 nm excitation, the downconverted red emission of the KYb2 F7 :Er 3+ nanocrystals pre-excited with the 980 nm laser was significantly enhanced. By manipulating the KYb2 F7 :Er 3+ host structure via substitution of cations such as Ca 2+, Ti 4+, Si 4+, Ge 4+, Y 3+, and Nd 3+ for Yb 3+ with optimized concentrations, the thermometric properties of KYb2 F7 :Er 3+ were greatly improved. The substitution of Ti 4+, Ge 4+, and Y 3+ has significantly improved the S R (for Ti 4+ both S A and S R are improved). The highest S A (0.0028 K −1 ) and S R (1158/ T 2 K −1 ) were obtained for KYb1.8 Ti0.15 F7 :Er 3+ and KYb1.8 Ge0.15 F7 :Er 3+, respectively. The mechanistic investigations revealed that the green and red UC emissions resulted from the three- and two-photon process, respectively. We believe that the substitution strategy could be a powerful tool for enhancing the thermometric properties of luminescent materials.